PRZEGLĄD PIŚMIENNICTWA - Nytko, Marcin (Wydział Prawa i Administracji UAM, 2006)
Introducing Market Economy Institutions and Instruments: The Role of Public Relations in Transition Economies, red. R. Ławniczak, Wydawnictwo piar.pl, Poznań 2005, ss. 253.